PENGELOLAAN BAHAN BAKU PASTRY PADA FOOD AND BEVERAGE DEPARTEMENT GRAND JATRA HOTEL PEKANBARU - Yuli Anggraini Junaidi; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Grand Jatra Hotel Pekanbaru is a five-star hotel in the middle of the city and Grand Jatra Hotel Pekanbaru produces various types of food dishes, from main courses to desserts, one of which is pastry. Before doing pastry production, there must be a procedure in the management of pastry raw materials first. The management of raw materials is a sequence before carrying out the production process of a food product. With that, this study aims to find out how the processes and constraints that occur in the Management of Pastry Raw Materials at the Food and Beverage Department of Grand Jatra Hotel Pekanbaru. The study used descriptive qualitative methods to analyze data using data collection techniques based on observation, interviews and documentation. Raw Material Management includes management in forecasting pastry production raw materials to time management of pastry raw materials in the process of ordering, using, to arrive at the warehouse. Based on the results of the study, it can be concluded that in the process of Managing Pastry Raw Materials has not run perfectly, there are still often misunderstandings between suppliers and purchasing parties. Keywords : Grand Jatra Hotel Pekanbaru, Raw Material Management, Pastry